2018
DOI: 10.1002/slct.201801180
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Stability of Lipid/Protein‐Coated Nanomaterials in Salt and Sucrose Solutions

Abstract: Considering the importance of surface chemistry in the colloidal stabilization of gold nanorods (AuNRs), we designed AuNRs in two physiologically relevant, salt and salt‐free aqueous solutions to validate its role in colloidal stability. Here, we show that AuNRs coated with cationic lipid/lipid‐binding protein composite materials is stable in both phosphate‐buffered saline (PBS) and sucrose solution (200 mM), but not in deionized water. Salting‐in effects of proteins explain the relatively better stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The preparation of catHDL was described in a previous report 30,33 . In brief, POPC and DOTAP solutions in ethanol were mixed in a round-bottom flask in a molar ratio of 7:3.…”
Section: Cathdl Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of catHDL was described in a previous report 30,33 . In brief, POPC and DOTAP solutions in ethanol were mixed in a round-bottom flask in a molar ratio of 7:3.…”
Section: Cathdl Preparationmentioning
confidence: 99%
“…30 The nanodevice is composed of a gold nanorod (AuNR) and a cationic highdensity lipoprotein (HDL) (Figure 1A). 33,34 The surface of the AuNR was coated with an HDLoriginated lipid-protein complex layer. HDLs serve as carriers of cholesterol in the human body and as modulators of lipid rafts, and cholesterol affinity reduces inflammation by cholesterol efflux from B cells.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is consistent with that reported in the literature, where it revealed that the lipoprotein mutant with a cationic lipid and a lipid binding protein could stabilize AuNRs based on salting-in effects by PBS. 30 Subsequently, owing to the formation of a specific steric structure with high affinity between the anti-LDL aptamer and LDL, LDL detaches from the PSS-AuNR surface and re-aggregation of PSS-AuNRs occurs when the anti-LDL aptamer is added to the salt buffer solution (Fig. 1E).…”
Section: Fabrication and Characterization Of The Discriminator Platformmentioning
confidence: 99%
“…First, we established that pm-AuNRs bind to Lo-phase GUVs much more efficiently than to Ld-phase GUVs, which is in accordance with the rule described above (Figure S1). 30 Subsequently, we investigated the effect of pm-AuNR on the membrane phase of Lo/Ld GUVs. The type of the phase is generally identified on the basis of the domain shape, which is circular for Lo domains and noncircular for So domains (Figure 2A).…”
mentioning
confidence: 99%
“…First, we established that pm-AuNRs bind to Lo-phase GUVs much more efficiently than to Ld-phase GUVs, which is in accordance with the rule described above (Figure S1). Subsequently, we investigated the effect of pm-AuNR on the membrane phase of Lo/Ld GUVs. The type of the phase is generally identified on the basis of the domain shape, which is circular for Lo domains and noncircular for So domains (Figure A). , When pm-AuNRs were added to Lo/Ld-GUVs (DOPC/DPPC/cholesterol = 2:2:1), their circular Lo-phase domains (Figure B) instantaneously diminished and noncircular (string-shaped) domains emerged on the surface of GUVs (Figure C, Figure S2A, S3A).…”
mentioning
confidence: 99%